2019
DOI: 10.3390/cancers11040473
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Potential of Saliva-Based Test to Detect HPV-16-Driven Oropharyngeal Cancer

Abstract: The incidence of human papillomavirus (HPV)-positive oropharyngeal cancer (OPC) is rising in high-income countries, including Australia. Increasing evidence suggests that accurate HPV testing is pivotal for clinical decision making and treatment planning in these patients. Recently, the eighth edition of the American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) tumor–node–metastasis (TNM) staging system for OPC (based on the p16INK4a (p16) status) was proposed and has been imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…It demonstrates that a screened individual can receive significantly less morbid treatment than would be required for the standard presentation at a more advanced stage. This report and previous studies (8,11,12,22), support the value of a salivary oral rinse test as a potential screening tool. Unlike previously published work, our study is the first to demonstrate that continuous monitoring of HPV-16 DNA in salivary oral rinse samples can detect occult OPC.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It demonstrates that a screened individual can receive significantly less morbid treatment than would be required for the standard presentation at a more advanced stage. This report and previous studies (8,11,12,22), support the value of a salivary oral rinse test as a potential screening tool. Unlike previously published work, our study is the first to demonstrate that continuous monitoring of HPV-16 DNA in salivary oral rinse samples can detect occult OPC.…”
Section: Discussionsupporting
confidence: 80%
“…Total DNA was extracted from salivary oral rinse and tonsillar tissue samples using the QIAmp DNA Mini Kit (Qiagen, Germantown, MD, USA) as per manufacturer's protocol. For detection of HPV-16 genotyping, the qPCR assay targeting the opening reading frame (ORF) region of HPV16 E6/7 was carried out with the QuantStudio TM 7 Flex Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) as described previously (11,12). For quantification of HPV-16 DNA viral copies in salivary oral rinse and tissue samples, a standard calibration curve was generated using qPCR by plotting threshold cycle (Ct values) against the logarithm of the copy number of 8fold serially diluted (1 × IMMUNOHISTOCHEMISTRY H&E (Haemotoxylin and Eosin stains) staining on formalin-fixed paraffin-embedded (FFPE) slide was performed to investigate the cellular and tissue structure/morphology.…”
Section: Hpv-16 Dna Qpcr Analysismentioning
confidence: 99%
“…High-risk HPV DNA integration into the human cellular genome, followed by the upregulation of E6 and E7, often trigger malignant transformation of cells in cervical and anal cancer as well as in OPC [48,49]. Our previous work indicated that most HPV16 OPC cases showed evidence of integration (either partially or fully) in both saliva and tumour fractions [15,50]. However, little attention to date has been paid to investigate whether HPV integration is a necessary step in the carcinogenesis of OC.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that the importance of additional HPV testing in HPV-associated cancer diagnosis and prognosis [13]. Previous studies have demonstrated that the presence of HPV DNA in tumour tissues is significantly correlated with HPV DNA positivity in saliva samples collected from OPC patients, thus suggesting the use of salivary HPV as a biomarker for the detection of HPV DNA in OPC patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The oropharynx can be considered as the hotspot of HPV-driven cancers in the head and neck region, as the vast majority of these cancers arise in the palatine tonsils and base of the tongue [6,7]. These cancers have clinically and biologically distinct features from their HPV-negative counterparts in terms of their gene expression profiles, mutation burden, epigenetic profiles, and treatment response [8][9][10][11].…”
Section: Hpv-driven Head and Neck Cancermentioning
confidence: 99%